Chromosomal abnormalities in a decade of prenatal testing at the Department of Obstetrics and Pathology of Pregnancy Medical University of Lublin - Krzyżanowski, Arkadiusz; Gęca, Tomasz; Kwiatek, Maciej; Kwaśniewska, Anna (Polish Journal of Public Health, 2015)
Introduction. Chromosomal abnormalities, one of the leading causes of pregnancy complications, attract attention of both researchers and clinicians. They use two approaches to identify chromosomal abnormalities, namely screening and diagnostic tests. Ultrasonography is a very reliable screening and diagnostic tool, but the only way to determine if there are any chromosomal defects in the fetus, is performing one of invasive diagnostics tests chorionic villus sampling (CVS), cordocentesis or amniocentesis. Unfortunately, these invasive diagnostic procedures carry a potentially high risk of complications. Using amniocentesis means a procedure-related miscarriage risk at a rate of about 0.5-1%.Aim. The aim of this paper was to present our own experience, results in performing amniocentesis and a review of the literature.Material and methods. During a 10-year period 237 mid-trimester, transabdominal amniocenteses were performed.Results. The follow-up revealed one spontaneous abortion within seven days after the procedure. Premature delivery occurred in fourteen cases (two of them with chromosomal abnormalities). No neonatal deaths related to amniocentesis were noticed. Chromosomal abnormalities were detected in 33 patients.Conclusions. In the group with chromosomal abnormalities the main indications to perform amniocentesis were: improper ultrasound scan and the first trimester biochemical, noninvasive screening tests. This is a proof that modern, non-invasive procedures like the first-trimester ultrasound scan and biochemical tests should be made available to every pregnant woman and not only to mothers’ aged >35 years or those with a poor obstetrics history.